1994
DOI: 10.1016/0163-6383(94)90024-8
|View full text |Cite
|
Sign up to set email alerts
|

Imitation, memory, and the representation of persons

Abstract: Imitation was tested both immediately and after a 24-hr retention interval in 6-week-old infants. The results showed immediate imitation, which replicates past research, and also imitation from memory, which is new. The latter finding implicates recall memory and establishes that 6-weekolds can generate actions on the basis of stored representations. The motor organization involved in imitation was investigated through a microanalysis of the matching response. Results revealed that infants gradually modified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
147
2
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 445 publications
(154 citation statements)
references
References 52 publications
3
147
2
2
Order By: Relevance
“…This activation may give rise to phantom sensations in at least a minority of individuals with limb aplasia. A very early use of action-observation as a basis for action planning is suggested by developmental studies that have shown that infants as young as 6 weeks old are capable of imitating a variety of distinct facial movements (40). On the other hand, gesture usage in congenitally blind people reportedly is comparable to that of sighted people, indicating a genetic component for the execution of communication-related hand and arm movements (41).…”
Section: Discussionmentioning
confidence: 99%
“…This activation may give rise to phantom sensations in at least a minority of individuals with limb aplasia. A very early use of action-observation as a basis for action planning is suggested by developmental studies that have shown that infants as young as 6 weeks old are capable of imitating a variety of distinct facial movements (40). On the other hand, gesture usage in congenitally blind people reportedly is comparable to that of sighted people, indicating a genetic component for the execution of communication-related hand and arm movements (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infants produce gestures without prompt after a delay, suggesting they are initiating social interaction rather than simply copying actions [96]. In humans, so-called deferred imitation is present (after a 24 h delay) from at least six weeks of life [31,97], and in some macaque infants, it is present (after a 60 s delay) in the first week of life [53], which indicates that these gestures are communicative and under voluntary control rather than reflexive fixed action patterns.…”
Section: Core Questions and Misunderstandings About Neonatal Imitatiomentioning
confidence: 99%
“…According to this view, matching should occur for only a few evolutionarily privileged gestures, that is, gestures that are, putatively, fixed and stereotypic, and produce a matching response that is time-locked to the modelled 'trigger' action [95]. This prediction, however, has been tested and has not been supported: infants produce a range of gestures which are not stereotyped, actions which have never been seen before are matched, corrections are made to initial attempts, and responses are not time-locked to modelled actions [31,32,40]. In addition, infants produce gestures without prompt after a delay, suggesting they are initiating social interaction rather than simply copying actions [96].…”
Section: Core Questions and Misunderstandings About Neonatal Imitatiomentioning
confidence: 99%
See 2 more Smart Citations